MODEL KEPEMIMPINAN DI PONDOK PESANTREN - Remiswal, Remiswal; Hasbi, Firqi; Diani, Yola Putri (UIN Imam Bonjol Padang, 2020)
Leadership plays an important role in an organization or institution. Leadership does not only play a role in directing and organizing the potential of organizational members through mutually formulated goals. However, leadership also plays a key role in regulating the rhythm of organizational movements, including Islamic boarding schools. The Islamic boarding school is an Islamic educational institution led by a kyai. As an organization, the level of success of education in Islamic boarding schools is very much influenced by the model and style of the leader. The results of the analysis of this study answered that the leadership model of Islamic boarding schools currently has a leadership model that tends to have individual-collective characteristics. It is known that the implementation of leadership in pesantren is still guided by individual kyai. Meanwhile, in another aspect, the Islamic boarding school is under the auspices of a foundation so that collective leadership collaboration is needed.